TUA TOSORA MOSQUE: A CULTURAL HERITAGE BUILDING AND ITS IMPACT ON TOSORA COMMUNITIES - Amhardianti Amhardianti; Syamsudduha Saleh; Syamzan Syukur (JICSA : Journal of Islamic Civilization in Southeast Asian, 2022)
This study aims to discuss about the old tosora mosque of Wajo Regency as a cultural heritage building and its influence on the Tosora community. The history of the development of Islam in South Sulawesi, especially in Wajo Regency, also contains one of the most valuable historical heritages of Islam which is a silent witness to the growth and development of Islamic teachings. This study uses descriptive qualitative research, as well as a multidisciplinary approach, namely theological, phenomenological, and historical approaches in studying the genealogy of the old Tosora mosque. Religious Tourism. Local community activities and local wisdom that are still being maintained can also support Cultural Tourism activities so that the attraction does not stop at historical sites, but the local wisdom of the community is also an attraction. Therefore, local wisdom such as weaving, mappadendang, and macera tappareng can be maintained as a support for cultural tourism.